Oral Hygiene Paliatif (Sebuah Laporan Kasus) - Eva Rista Machdalena; Tiodora Sinambela; Sarita Saraswati; Rona Cahyantari Merduaty (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Routine oral hygiene can increase the body's natural defenses because saliva contains enzymes that can help the digestive process and control the normal flora in the mouth area. So a study is needed that aims to compare nutritional intake and also the nutritional status of clients after oral hygiene interventions. This case report involved an elderly woman with palliative care, with a multipathological disease. Data was collected from interviews, observations and documentation. From the results of the study, it was found that the client was composmentis, blood pressure = 130/89 mmHg, pulse = 89 times/minute; breathing = 20 times/minute; temperature = 36.8 oC; oxygen saturation = 99%, the conjunctiva is not pale, the sclera is not icteric. Vesicular breath sounds in both lung fields, no crackles and wheezing. The abdomen is distended, there is no tenderness, the spleen is not palpable, the right abdominal region is palpable. Warm acral, bilateral pitting edema, there is a wound in the right pedis area. From ECOG (Eastern Cooperative Oncology Group) scoring, Grade 3 was obtained, Karnofsky's score was 50. After a CGA (Comprehensive Geriatric Assessment) examination, Barthel index scale = 1, braden scale = 15, MNA SF (Mini Nutritional Assessment - Short) Form) = 7, MNA LF (Mini Nutritional Assessment – Long Form) = 14 (malnutrition), SARC-F = 4 (predictive of sarcopenia), Frail scale = 4. On anthropometric examination, estimated body weight = 40 kg, height = 162 cm, upper arm circumference = 18 cm, upper arm circumference percentile = 60%; body mass index = 15.1 (underweight). The medical diagnosis was Cystic Ovarian Neoplasm, Bilateral Pedis Ulcer with nutritional deficit problems and risk of infection. Oral hygiene was carried out twice a day for 5 days. After oral hygiene treatment, it was found that the client's oral condition looked better and there was a significant increase in appetite.Keywords: oral hygiene; nutritional status; palliative ABSTRAK Oral hygiene secara rutin dapat meningkatkan pertahanan tubuh yang alami karena air liur mengandung enzim yang dapat membantu proses pencernaan dan mengontrol flora normal pada area mulut. Maka diperlukan studi yang bertujuan untuk membandingkan asupan nutrisi dan juga status nutrisi klien setelah dilakukan intervensi oral hygiene. Laporan kasus ini melibatkan lansia perempuan dengan perawatan paliatif, dengan penyakit multipatologis. Data dikumpulkan dari hasil wawancara, observasi dan dokumentasi. Dari hasil pengkajian didapatkan klien composmentis, tekanan darah = 130/89 mmHg, nadi = 89 kali/menit; pernafasan = 20 kali/menit; suhu = 36,8 oC; saturasi oksigen = 99%, konjungtiva tidak pucat, sklera tidak ikterik. Suara napas vesikuler di kedua lapang paru, ronkhi dan wheezing tidak ada. Abdomen buncit, nyeri tekan tidak ada, hepar lien tidak teraba, teraba masa regio abdomen kanan. Akral hangat, pitting edema bilateral, terdapat luka di daerah pedis dekstra. Dari scoring ECOG (Eastern Cooperative Oncology Group) didapatkan Grade 3, untuk skor Karnofsky didapatkan nilai 50. Setelah dilakukan pemeriksaan CGA (Comprehensive Geriatric Assessment), didapatkan Barthel Indeks scale = 1, braden scale = 15, MNA SF (Mini Nutritional Assessment – Short Form) = 7, MNA LF (Mini Nutritional Assessment – Long Form) = 14 (malnutrisi), SARC-F = 4 (prediktif sarcopenia), Frail scale = 4. Pada pemeriksaan antropometri didapatkan berat badan estimasi = 40 kg, tinggi badan = 162 cm, lingkar lengan atas = 18 cm, persentil lingkar lengan atas = 60%; index massa tubuh = 15,1 (underweight). Diagnosa medis adalah Neoplasma Ovarium Kistik, Ulkus Pedis Bilateral dengan masalah defisit nutrisi dan risiko infeksi. Oral hygiene dilakukan dua kali dalam sehari  selama 5 hari. Setelah dilakukan perawatan oral hygiene didapatkan kondisi oral klien tampak lebih baik dan terdapat peningkatan nafsu makan yang cukup signifikan.Kata kunci: oral hygiene; status nutrisi; paliatif